Aplikasi Beberapa Jenis Pupuk Kandang dan Varietas terhadap Pertumbuhan dan Hasil Mentimun (Cucumis sativus L.) - Sabarudin Sabarudin; Yagin Yagin; Rina Lesmana (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
The experiment was conducted to determine the effect of manure and varieties on growth and yield of cucumber. The experimental design used in this study was a randomized block design (RBD) factorial with four (4) factors and three (3) replicates. Factor I. Manure (P) consists of four treatments are: P0 = without fertilizer, PA = Manure Chicken, PK = Manure Goats, PS = Cow Manure. Factor II varieties (V) consists of two treatments are: V1 = Mercey F1, V2 = F1 Monza, in order to obtain 8 Interaction treatment. The parameters measured were plant length (cm), number of leaves (pieces), fruit length (cm), fruit diameter (mm), fruit weight (g). of the results showed that significantly affect manure crops 1-4 MST length, number of leaves 1-4 MST, fruit length, fruit diameter, fruit berta. Varieties significant effect on plant length 2-4 MST. The number of leaves 3-4 MST, fruit length, fruit diameter, fruit weight. While the length of interaction significantly affect plant 3-4 MST, MST 3-4 leaf number, fruit length, fruit diameter, fruit weight.